RHETORIC AS A TOOL FOR CONTROLLING CONFLICT: A DISCOURSE ANALYSIS PERSPECTIVE - Hakim, Arief Rahman; Huda, Miftahul; Nasrulloh, Nasrulloh (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
In the early 20th century, the landscape of Islamic scholarship was marked by intense intellectual debates and the challenge of reconciling classical traditions with modern perspectives. Against this backdrop, this study analyzes Amin al-Khuli's use of rhetoric in the editorial of the Qadla' Syar'i journal to reduce intellectual conflict and promote rational academic dialogue. Amin al-Khuli served as the editor-in-chief of the journal in 1922, during which he published a controversial article regarding the implementation of three talaq with one word, a topic that sparked significant debate and nearly led to the closure of the journal. In response to the controversy, al-Khuli employed a structured rhetorical approach in his editorial to assert the journal’s neutrality, reduce tensions, and foster constructive engagement with the readership. This research employs discourse analysis to examine the relationship between language and context in al-Khuli’s editorial strategies. The findings reveal that his rhetorical approach successfully positioned the journal as an impartial platform for scholarly discussion by emphasizing that published articles served as intellectual exercises rather than endorsements of particular viewpoints. His rhetorical strategies included intensification to reinforce neutrality, attenuation to minimize controversy, credibility-building techniques to establish trust, and emotional engagement to create a sense of inclusivity and participation. These rhetorical elements contributed to strengthening the tradition of open and rational academic discourse while bridging the gap between classical Islamic scholarship and modern intellectual thought. The study highlights the importance of effective rhetorical strategies in managing differences of opinion and sustaining academic integrity. However, it is limited to analyzing a single editorial text and does not fully explore the audience’s reception or its broader impact on Islamic legal thought. Future research is recommended to assess the long-term influence of such discourse on contemporary Islamic scholarship. This study contributes to the understanding of how rhetoric can be strategically employed in academic and public discourse, offering valuable insights for educators, policymakers, and media professionals in fostering inclusive and constructive dialogue.